Are socially responsible companies harder to arbitrage? - Arouri, Mohamed; Ayed, Sabrine; Gomes, Mathieu (Management international / International Management / Gestiòn Internacional, 2023)
We examine how corporate social responsibility (CSR) affects limits to arbitrage. Using a sample of S&P 500 firms from 2002 to 2020, our findings indicate that firms with high CSR performance are associated with a higher degree of limits to arbitrage. Those findings are confirmed when using only social and environmental dimensions, and when testing the relationship between CSR and each limits-to-arbitrage component separately. Our findings hold when using an alternative measure of limits to arbitrage and are robust to endogeneity checks. Our study suggests that CSR makes arbitrage activity harder and riskier, thereby leading to mispricing.